Double lumen esophagus: A rare complication of gastroesophageal reflux disease. Issue 2 (5th March 2013) - Samiullah, Sami; Samad, Fatima; Tang, Ying Margie; Abdullah, Neelofar; Marium, Marium; Shaikh, Zahf; Brelvi, Zamir; Wang, Weizheng
<x xml:space="preserve">Abstract</x> Double lumen esophagus or esophagogastric fistula is a very rare endoscopic finding. Approximately 11 cases have been reported in the past. Formation of an esophagogastric fistula is predisposed by previous esophagogastric surgery, persistent gastroesophageal reflux, esophageal ulcer or esophageal carcinoma. Dysphagia and odynophagia are common symptoms. Endoscopy is the procedure of choice for diagnosis. Symptomatic management is the mainstay of treatment. Early diagnosis andmanagement of gastroesophageal reflux is essential to prevent reflux‐related fistulas. We report the case of a 48‐year‐old man with a history of dysphagia who was found to have esophagogastric fistula on endoscopy. He was treated conservatively with proton pump inhibitors leading to symptomatic improvement.